Experimental estimation of the heat energy dissipated in a volume surrounding the tip of a fatigue crack - G. Meneghetti; M. Ricotta (Fracture and Structural Integrity)
Fatigue crack initiation and propagation involve plastic strains that require some work to be done on the material. Most of this irreversible energy is dissipated as heat and consequently the material temperature increases. The heat being an indicator of the intense plastic strains occurring at the tip of a propagating fatigue crack, when combined with the Neuber’s structural volume concept, it might be used as an experimentally measurable parameter to assess the fatigue damage accumulation rate of cracked components. On the basis of a theoretical model published previously, in this work the heat energy dissipated in a volume surrounding the crack tip is estimated experimentally on the basis of the radial temperature profiles measured by means of an infrared camera. The definition of the structural volume in a fatigue sense is beyond the scope of the present paper. The experimental crack propagation tests were carried out on hot-rolled, 6-mm-thick AISI 304L stainless steel specimens subject to completely reversed axial fatigue loading.